PKM PENGOLAHAN ABON TULANG IKAN BANDENG PADA KELOMPOK WANITA TAMBAK DI DESA TAMANGAPA KECAMATAN MA’RANG KABUPATEN PANGKEP - Ernaningsih, Ernaningsih; Kasmawati, Kasmawati; Ilmiah, Ilmiah (JURNAL PENGABDIAN MASYARAKAT KAUNIAH, 2023)
Tamangapa Village, Pangkep Sul-Sel Regency, is the center of the milkfish producing area. Besides being sold in whole form, milkfish is also made by the community to make milkfish products without thorns or what is known as BATARI. The pond farmer group together with the community partnership program team from the Indonesian Muslim University (UMI) are looking for a solution to the problems mentioned above, so the efforts made are the Utilization of Milkfish bones (Chanos Chanos) into Shredded Products of High Economic Value. Service activities are intended to provide knowledge and skills of members of the Pond Women's Group through counseling or training and mentoring to be able to produce shredded to the packaging stage. Community service activities were carried out on November 18, 2022 in Tamangapa Village with group partners "Tani Tambak. The method used in the training is a participatory training method, which involves partners in discussion activities, is actively involved in milkfish bone shredding activities. The output of this activity partners can be able to process milkfish spines into shredded to packaging, understand strategies in marketing and promotion as well as the legality of pirt business and Halal Certificates